Countervailing Duties on Transnational Subsidies: WTO Review of the EU Case Against Indonesian Stainless Steel - Sefriani Sefriani; Muhammad Iswan; Seguito Monteiro (Sriwijaya Law Review, 2025)
Transnational subsidies are financial assistance provided by a country to industries operating in another country in order to increase trade on a global scale. Transnational subsidies are used frequently in practical cooperation between countries. However, since the European Union imposed countervailing duties on products from Egypt and subsequently on Indonesian stainless-steel products, the concept of transnational subsidies has given rise to debate regarding subsidy regulations in international trade law. This research is aimed at analyzing the existence of transnational subsidy regulations under WTO regulations and the validity of applying the European Union's compensation import duty burden to stainless steel products from Indonesia which are suspected of receiving financial assistance from China through a cooperation project between the Chinese-Indonesian government. This research is research normative juridical which uses statutory, conceptual, case and philosophical approaches. The research results show that the transnational subsidy provisions regulated in the EU FSR are in accordance with the aim of prohibiting subsidies in international trade but are not recognized in the provisions of the SCM Agreement and GATT 1994.